SIMBOLISME SERANGGA SEBAGAI REPRESENTASI ANCAMAN EKSISTENSIAL DALAM SERIAL NETFLIX “3 BODY PROBLEM” - Azky Dujak Sakwa; Rocky Prasetyo Jati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study analyzes the use of insect symbolism in the Netflix series 3 Body Problems, which is adapted from a novel by Liu Cixin. In the series, insects are used as symbols with deep meaning, representing themes of resilience, existence, and interspecies interaction. Using Roland Barthes' semiotic approach, this study aims to explore the denotative and connotative meanings of insect symbols and how these symbols convey social and philosophical messages to the audience. Through the analysis of several scenes featuring insects, the research shows that the symbol not only functions as a visual element, but also as a means to reflect on social issues such as injustice, existential threat, and environmental crisis. The research findings reveal that insects in 3 Body Problems function as a metaphor for human resilience in the face of great challenges, as well as a symbol of Tricolaris' pessimistic view of humanity. This research provides insights into how symbolism in media can enrich the audience's understanding of social issues and influence the way they view the world.